Toward Bridging the Conceptual Gap in Pancasila Education: A Multi-Source Needs Analysis for Interactive Multimedia Design - Arya Chandra Kirana; Wuri Wuryandani (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2026)
This study addresses a persistent conceptual gap in fifth-grade Pancasila Education specifically in learning norms, rights, and obligations by conducting a systematic multi-source needs analysis for interactive multimedia design. Grounded in Mayer’s Cognitive Theory of Multimedia Learning and Piaget’s developmental framework, the study employed a qualitative descriptive approach in which descriptive statistics from student questionnaires were used to quantify identified needs and strengthen qualitative interpretations drawn from interviews and observations. Data were collected from 175 students and 7 classroom teachers across seven elementary schools in Ngaglik District, Sleman Regency, Yogyakarta, from January to March 2026, using purposive sampling. Three research questions guided the study, addressing learning process conditions, conceptual understanding, and multimedia needs. Findings revealed a significant pedagogical gap between students' high motivational readiness (93.1%) and instructional quality, as lecture-based methods dominated with minimal use of interactive media. Students' conceptual understanding averaged only 50.1% across six indicators, reflecting a systematic gap between declarative knowledge and applied understanding a dual limitation explicable through the convergent application of CTML and Piaget's concrete operational framework. All students (100%) expressed a need for accessible and engaging learning media, with over 94% requesting interactive features such as animations, quizzes, and collaborative tools, unanimously endorsed by all seven teachers and corroborated by the complete absence of purpose-built multimedia in all observed schools. Unlike prior studies relying on single data sources or broad Pancasila themes, this study contributes a triangulated, context-specific needs profile and theoretically grounded design specifications to advance interactive multimedia development for this underexplored topic and grade level.